Breastfeeding support for adolescent mothers: similarities and differences in the approach of midwives and qualified breastfeeding supporters - Burt Susan; Dykes Fiona; Moran Victoria; Shuck Christina (BMC, 2006)
Abstract Background The protection, promotion and support of breastfeeding are now major public health priorities. It is well established that skilled support, voluntary or professional, proactively offered to women who want to breastfeed, can increase the initiation and/or duration of breastfeeding. Low levels of breastfeeding uptake and continuation amongst adolescent mothers in industrialised countries suggest that this is a group that is in particular need of breastfeeding support. Using qualitative methods, the present study aimed to investigate the similarities and differences in the approaches of midwives and qualified breastfeeding supporters (the Breastfeeding Network (BfN)) in supporting breastfeeding adolescent mothers. Methods The study was conducted in the North West of England between September 2001 and October 2002. The supportive approaches of 12 midwives and 12 BfN supporters were evaluated using vignettes, short descriptions of an event designed to obtain specific information from participants about their knowledge, perceptions and attitudes to a particular situation. Responses to vignettes were analysed using thematic networks analysis, involving the extraction of basic themes by analysing each script line by line. The basic themes were then grouped to form organising themes and finally central global themes. Discussion and consensus was reached related to the systematic development of the three levels of theme. Results Five components of support were identified: emotional, esteem, instrumental, informational and network support. Whilst the supportive approaches of both groups incorporated elements of each of the five components of support, BfN supporters placed greater emphasis upon providing emotional and esteem support and highlighted the need to elicit the mothers' existing knowledge, checking understanding through use of open questions and utilising more tentative language. Midwives were more directive and gave more examples of closed questions. These differences could reflect the considerable emphasis upon person-centred approaches within the BfN curriculum and, in the case of midwives, the bureaucratic and institutional constraints upon them making it difficult, if not impossible, to take time and touch base with women. Conclusion Follow up ethnographic work is required to assess the differences in the supportive approaches of BfN supporters and midwives in the practice areas. Such research, which specifically focuses upon how the different approaches are received and experienced by parents, is required before meaningful policy and practice recommendations can be made.